Intellectual stress as a predictor of Type D personality among a sample of graduate students at King Abdulaziz University in Jeddah - Alomari, Esraa Saad; Elsayed, Fatma Khalifa (Journal of Educational and Psychological Sciences, 2025)
Intellectual stress and Type D personality are significant variables that influence Graduate students’ psychological well-being and academic performance. This study aimed to evaluate the levels of Intellectual stress and Type D personality among a sample of Graduate students at King Abdulaziz University in Jeddah. Additionally, the research sought to explore the association between Intellectual stress and Type D personality, assess variations in these variables based on gender and academic stage, and examine the predictive capacity of Intellectual stress in relation to Type D personality. The study involved a sample of (121) graduate students, consisting of (41) males and (80) females. The instruments utilized included the Intellectual Stress Scale, developed by Abdul Abbas Shati and Fatima Munadi (2019/2020), and the Type D Personality Scale (DS-14), created by Denollet (2005) and translated by Fatima Najjar and Wissam Buraik (2016). A descriptive correlational comparative method was employed for data analysis. Results demonstrated moderate levels of both Intellectual stress and Type D personality among the participants. Additionally, a positive correlation was identified between Intellectual stress and Type D personality. No significant differences were found in the levels of Intellectual stress and Type D personality based on gender or academic stage. Furthermore, the findings indicated that Intellectual stress serves as a significant predictor of Type D personality. Based on these findings, the study recommends the implementation of counseling and therapeutic programs aimed at alleviating the effects of Intellectual stress on students, enhancing their psychological health, and developing strategies to improve academic performance while reducing the negative impacts of Type D personality.